2018
DOI: 10.1073/pnas.1711122115
|View full text |Cite
|
Sign up to set email alerts
|

Climate vulnerability and resilience in the most valuable North American fishery

Abstract: Managing natural resources in an era of increasing climate impacts requires accounting for the synergistic effects of climate, ecosystem changes, and harvesting on resource productivity. Coincident with recent exceptional warming of the northwest Atlantic Ocean and removal of large predatory fish, the American lobster has become the most valuable fishery resource in North America. Using a model that links ocean temperature, predator density, and fishing to population productivity, we show that harvester-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 40 publications
6
122
0
Order By: Relevance
“…However, despite the wealth of work undertaken in marine environments on the causes of longer‐term biological change, the effects of these two drivers have traditionally been considered in isolation, and when in concert only at the population scale (e.g. Perry et al, ; Planque et al, ; Kjesbu et al, ; Le Bris et al, ). Here, we show that fishing can induce shifts in purple wrasse individual‐level biocomplexity, namely the expression of growth thermal reaction norms.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the wealth of work undertaken in marine environments on the causes of longer‐term biological change, the effects of these two drivers have traditionally been considered in isolation, and when in concert only at the population scale (e.g. Perry et al, ; Planque et al, ; Kjesbu et al, ; Le Bris et al, ). Here, we show that fishing can induce shifts in purple wrasse individual‐level biocomplexity, namely the expression of growth thermal reaction norms.…”
Section: Discussionmentioning
confidence: 99%
“…The thermally mediated dilution hypothesis is not the only potential explanation of declining recruitment density. Declining reproductive output (Koopman, Westgate, & Siders, ), recruit‐per‐egg ratios (Le Bris et al, ), and lipid‐rich prey of larvae (Carloni et al, ) have been proposed as mechanisms driving declines in recruitment density under warming conditions. Consequently, Le Bris et al () project that recruitment in a warming Gulf of Maine will show widespread declines across the American lobster's range with only slight increases projected for the northeastern Gulf of Maine.…”
Section: Discussionmentioning
confidence: 99%
“…Declining reproductive output (Koopman, Westgate, & Siders, ), recruit‐per‐egg ratios (Le Bris et al, ), and lipid‐rich prey of larvae (Carloni et al, ) have been proposed as mechanisms driving declines in recruitment density under warming conditions. Consequently, Le Bris et al () project that recruitment in a warming Gulf of Maine will show widespread declines across the American lobster's range with only slight increases projected for the northeastern Gulf of Maine. The assumption of reduced recruitment naturally leads to the conclusion that the Gulf of Maine lobster fishery is on the precipice of an imminent decline (Le Bris et al, ; Oppenheim, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the value of fisheries management measures that preserve stock size and age structure, protect reproductive females and spawning congregations, and maintain abundance for enhancing the resilience of fish and invertebrate populations to climate impacts (Pershing et al 2015a;Le Bris et al 2018). As such, recognition that climate conditions can play a role in stock outcomes should not be viewed as an opportunity to relax the management standards established by the MSFCMA.…”
Section: Environmental Changementioning
confidence: 99%